Peningkatan Kompetensi Siswa SMK Dalam Bidang Akuntansi Melalui Pelatihan Accurate - Astrid Rudyanto; Ariesta Tika Kinanti PSP; Jenny Vivianti; Debora Setopo; Fanny Anggreani6; Silvy Christina; Nico Alexander (FEB-UP Press, 2024)
Competence is a crucial aspect in the realm of employment. An individual is deemed competent when they exhibit a mastery of knowledge within their respective field. This is precisely the objective that SMK Strada Daan Mogot aims to accomplish, particularly in the field of accounting. The institution endeavors to ensure that students specializing in accounting acquire the necessary competence through training sessions. To this end, a service was implemented to facilitate the development of accounting competence among the students of SMK Strada Daan Mogot, utilizing the Accurate software. The approach adopted in this service encompasses tutorials, discussions, and mentoring sessions. All eleventh-grade students participated in this training initiative. The outcome of this service is evident in the enhanced expertise of the students in utilizing the Accurate software, which is evaluated through post-mentoring assessments. Those students who successfully pass the assessment will be awarded a certificate of competence in Accurate software, thereby enhancing their employability prospects upon graduation.